Neutrosophic Evaluation of Conventional and Non-Conventional Resources in Higher Education - Walter Cente Pérez; Hortencio Flores Flores; Manuel Cesar Vildoso Villegas; Adán Humberto Estela Estela; Carlos Fretel Martínez; Virgilio Vildoso Gonzales; Eli Carrillo Vásquez (Neutrosophic Sets and Systems)
Evaluating the effectiveness of teaching resources in higher education faces the challenge of inherent subjectivity and ambiguity in pedagogical processes. Existing studies often oversimplify the complexity of the educational phenomenon. This research proposes an innovative model combining neutrosophic theory with multicriteria decision-making methods (specifically SVNLOWAD-TOPSIS) to simultaneously assess truth, falsity, and indeterminacy in resource effectiveness. The methodological framework, acknowledging the plithogenic nature of educational processes, uses a mixed-method design integrating expert perceptions synthesized via neutrosophic operators. A case study evaluating four resource types—traditional classes, online platforms, virtual simulations, and Project-Based Learning (PBL)—demonstrated that PBL is the most effective, followed by online platforms and virtual simulations, while traditional classes were least effective. The model effectively managed uncertainty, offering a robust tool for informed decision-making on selecting teaching resources in complex educational contexts and enriching pedagogical debate with a formal language for uncertainty.